Pilot study to assess measures to be used in the prospective audit of the management of foot ulcers in people with diabetes. Issue 1 (3rd September 2014) - Holman, N.; Young, B.; Stephens, H.; Jeffcoate, W.; the members of the National Foot Care Audit Steering Group
Abstract Aim To design and test a methodology for assessing aspects of the management of foot disease in diabetes. Methods A national working group devised pilot datasets that may be used to document the process of management of active ulceration. Participating volunteer specialist units throughout England were required to characterize newly presenting people with diabetic foot ulcers using a standard questionnaire comprising the dataset and to document outcomes at 6 and 12 months. Semi‐structured interviews were later conducted with the volunteers at the units. Results A total of 23 units recorded baseline data on 652 people with incident foot ulcers; valid outcome data were available for 541 people (83.0%). Of the 541 index ulcers, 351 (64.9%) healed within 24 weeks, with a median time to healing of 63 days. Ulcer site and depth and peripheral arterial disease were associated with differing ulcer healing rates. By contrast, baseline demographic characteristics were not independently associated with healing. These were used to calculate a standardized case‐mix adjusted healing ratio. In most units data collection took < 10 min per person, but participants reported that the burden of local data collection was still excessive. Conclusion This study confirmed the feasibility of routine multi‐unit comparative assessment of care of the foot in diabetes, including the generation of meaningful service reports, but for general use the burden of local data collection will need to be reduced (e.g. by using linkage to existing national data collections).